Peripheral Artery Disease in Acute Ischemic Stroke Patients Treated With Endovascular Thrombectomy; Results From the MR CLEAN Registry - Pirson, France A. V.; Hinsenveld, Wouter H.; Staals, Julie; de Ridder, Inger R.; van Zwam, Wim H.; Schreuder, Tobien H. C. M. L.; Roos, Yvo B. W. E. M.; Majoie, Charles B. L. M.; van der Worp, H. Bart; Uyttenboogaart, Maarten; Lycklama à Nijeholt, Geert J.; Schonewille, Wouter J.; et al. (Frontiers in Neurology, 2020)
Background and Purpose: Though peripheral artery disease (PAD) is a well-known risk factor for ischemic events, better outcomes have been described in acute ischemic stroke patients with co-existing PAD. This paradoxical association has been attributed to remote ischemic preconditioning (RIPC) and might be related to better collateral blood flow. The aim of this study is to compare outcomes after endovascular thrombectomy (EVT) in acute stroke patients with and without PAD and to assess the relation between PAD and collateral grades. Methods: We analyzed acute ischemic stroke patients treated with EVT for an anterior circulation large artery occlusion, included in the Dutch, prospective, multicenter MR CLEAN Registry between March 2014 and November 2017. Collaterals were scored on CT angiography, using a 4-point collateral score. We used logistic regression analysis to estimate the association of PAD with collateral grades and functional outcome, assessed with the modified Rankin Scale (mRS) at 90 days. Safety outcomes included mortality at 90 days, symptomatic intracranial hemorrhage, and stroke progression. Results: We included 2765 patients for analysis, of whom 254 (9.2%) had PAD. After adjustment for potential confounders, multivariable regression analysis showed no association of PAD with functional outcome (mRS cOR 0.90 (95% CI, 0.7-1.2), collateral grades (cOR 0.85, 95% CI 0.7-1.1), or safety outcomes. Conclusion: In the absence of an association between the presence of PAD and collateral scores or outcomes after EVT, it may be questioned whether PAD leads to RIPC in patients with acute ischemic stroke due to large vessel occlusion.